Use of Information Technology in Counting (Situng) and Recapitulating (Recapitalized) Votes for the 2024 Election: - Hidayatun Indriyani; Agata Meyer (Focus Journal : Law Review, 2023)
General elections are a concrete manifestation of the implementation of democracy in Indonesia which provides a role for every citizen to be able to directly participate in selecting public officials. Democracy and democratic elections are â€œqonditio sine qua nonâ€, the one can not exist without the others. In the sense that elections are interpreted as a procedure to achieve democracy or a procedure to transfer peopleâ€™s sovereignty to certain candidates to occupy political positions in a country. Based on Law Number 7 of 2017 concerning General Elections (Election Law), information on election results can be obtained after going through several stages and requiring a long waiting time. This is because the vote counting and recapitulation system still adopts conventional methods. In principle, the process for the counting and recapitulation system can be flowed as follows: After the voting is complete, then the vote count is carried out at the TPS level and followed by filling out the vote counting certificate manually with a large number of copies. After that it was sent to the District level for manual recapitulation and filling out the recapitulation certificate with a large number of copies. The recapitulation process, like in the Kecamatan, takes place and is tiered at the District/City level, Provincial level and National level. With a process like this, in addition to the potential for errors caused by human error and it also takes quite a long time which then has the potential for fraud to occur so that it requires the use of adequate information technology in the process.